The ABC of reproductive intentions: a mixed-methods study exploring the spectrum of attitudes towards family building. Issue 5 (3rd March 2022) - Grace, B; Shawe, J; Johnson, S; Usman, N O; Stephenson, J
Abstract: STUDY QUESTION: What are the intentions of men and women of reproductive age in the UK regarding reproduction and family building? SUMMARY ANSWER: We identified six main categories of people; Avoiders, Betweeners, Completers, Desirers, Expectants and Flexers, for whom reproduction education strategies should be tailored differently to suit intentions. WHAT IS KNOWN ALREADY: Several studies have highlighted poor fertility awareness across men and women of reproductive age. As the average age of first-time parents continues to rise, there has been a concerted effort from educators, healthcare professionals, charities, reproductive health groups and government policymakers, to improve fertility awareness. In order to ensure that these messages are effective and to deploy the best strategies, it is important to understand people's reproductive health needs. This study therefore aimed to explore different reproductive intentions to aid tailoring of information to help individuals and couples achieve their family building desires. STUDY DESIGN, SIZE, DURATION: We conducted a mixed-method study via a UK-wide cross-sectional survey with 1082 participants and semi-structured interviews of 20 women and 15 men who agreed to follow-up interviews. Interviews lasted an hour on average. Ethics approval from UCL Research Ethics Committee. PARTICIPANTS/MATERIALS, SETTING, METHODS: Survey participants were recruited nationwide via online newspaper and social media adverts. Interviewees were purposely sampled to include men and women from the reproductive age range (18–45 years), varying ethnicity and education background. Survey data were analysed using the Minitab statistical software package. Interview data were transcribed and analysed using the framework method. MAIN RESULTS AND THE ROLE OF CHANCE: From the survey and interviews, we identified six key categories of people, grouped alphabetically, in a user-friendly manner to highlight a spectrum of reproductive intentions: Avoiders describes respondents who have no children and do not want to have children in the future; Betweeners describes those who already have child(ren) and want more in the future but are not actively trying to conceive; Completers describes those who have child(ren) but do not want more; Desirers describes those who are actively trying to conceive or plan to have child(ren) in the future; Expectants describes those who were pregnant at the time of the study; and Flexers describes those who may or may not already have and are unsure but or open to having child(ren) in the future. Analysis of survey data identified the following proportions in our study: Avoiders, 4.7%; Betweeners, 11.3%; Completers, 13.6%; Desirers, 36.9%; Expectants, 4.1%; and Flexers 28.4% and 2.4% preferring not to answer. There was one 'other' group from qualitative analysis, who would like to have children in the future but were unsure whether they could or had changing views. We recommend classifying as 'Desirers' or 'Flexers' for the purposes of fertility education. A majority of the survey population were trying to get pregnant; were pregnant; or planning to have a child in the future—whether actively, passively or simply open to the idea, with interviews providing deep insights into their family building decision-making. LIMITATIONS, REASONS FOR CAUTION: Due to the online recruitment method, there may be a bias towards more educated respondents. WIDER IMPLICATIONS OF THE FINDINGS: We developed a user-friendly, alphabetical categorization of reproductive intentions, which may be used by individuals, healthcare professionals, educators, special interest groups, charities and policymakers to support and enable individuals and couples in making informed choices to achieve their desired intentions, if and when they choose to start a family. STUDY FUNDING/COMPETING INTEREST(S): There was no external funding for this study. The authors report no competing interests. TRIAL REGISTRATION NUMBER: N/A.